Sexualidade e deficiência física: um olhar reflexivo sobre a sexualidade da pessoa com deficiência física - CARDOSO, Tacimira Ferreira (2019)
The present research entitled "Sexuality and Physical Deficiency: A reflective look at the sexuality of the person with physical deficiency" was intends to understand how the sexuality of the person with physical deficiency is seen by the society itself? Taking into account that sexuality is part of the life of any human being, being the person with or without the disability, the research seeks to analyze specifically the following questions: What conceptions and constructions were produced by the person with physical deficiency about sexuality? What causes the discomfort in discussing the sexuality of the person with physical disability? From a qualitative research with an instrument the collection of data by interviews and bibliographical collections from authors such as: Foucault (1988), Maia (2011) and (2006), Silva (1987), Paula, Regen e Lopez (2011), Aranha (2003) among others. The great difficulty of the physically deficiency person to conceive sexuality as being something natural and intrinsic to any human being is linked to the discrimination that these people suffer and that causes them to not develop self-confidence and appreciation of their body, this generates a psychosocial obstacle that consequently prevents them from being inserted in a social environment thus delaying the exercise of sex life. Talking about sexuality with children, for a significant portion of parents is uncomfortable, this discomfort is even greater when it comes to parents of people with disabilities. Whereas, the idea of asexuality linked to people with disabilities is still very much present in the family environment. In order to adequately contemplate sexuality education, it is necessary for parents, teachers and the disabled person himself to have a broad notion of sexuality to abandon prejudice and discrimination directed at people with disabilities, since the sexual impulses of pleasure, desire and eroticism due to sexuality deserve to be known and preserved, regardless of the limitations existing with respect to the material body. It would also be interesting to provide a training in the field of special education, specifically in the area of pedagogy, on education for sexuality to teachers, since they still have difficulties dealing with sexuality with people with.